Manajemen Peserta Didik sebagai Upaya Pencapaian Tujuan Pendidikan - Zainur Arifin (Program Pascasarjana Universitas Pesantren Tinggi Darul Ulum (Unipdu) Jombang, 2022)
Student management as a process that regulates all forms of student activity becomes a measure of success in an effort to achieve educational goals effectively and efficiently. The purpose of student management is to regulate all forms of activities that support the learning process so that students become orderly so that they have an impact on overall educational goals. The success of education as a form of discipline among students in conditions that match their attitudes and behavior with the values ??and rules of the madrasa. Madrasas need to do their best to enforce the rules so that they can be a comfortable place for students to learn. To take disciplinary action, the teacher must consider the psychological aspects of each student. With the library research method, this study shows that student management produces activities that can support the development of student potential in the form of providing services to students in an educational institution, both inside and outside of classroom learning hours; student development can be carried out on new student orientation, discipline development by producing student attitudes, appearance, and behavior in accordance with the order of values, norms, and applicable provisions; The realization of student management has three main tasks that must be considered, namely acceptance of new students, learning progress activities, and guidance and discipline development.